Ghana and Togo under colonial rule, in Government reports, 1843-1957. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
Ghana and Togo were known by the colonial Government as the Gold Coast and British Togoland. These countries' records are published together because Togoland included land which is now part of Ghana. The Gold Coast and British Togoland were managed by the government departments who wrote these progress reports. The statistics for Ghana, but not Togo, are included in Colonial Africa in official statistics, 1821-1953. These reports explain why those statistics are at the levels recorded. The contents pages at the front of each report list the departments which existed at that time. Comparing the contents pages reveals how the structure of the colonial government changed over time.
Date range: 1843-1957.
Keywords: Ghana -- Politics and government -- To 1957.; Togo -- Politics and government -- 1922-1960.